Post Caesarean Section Wound Healing among Postpartum Women who Consumed Boiled Eggs - Sulistiorini; Shinta Novelia; Siti Syamsiah (KHD-Production, 2022)
In Indonesia, there is an increase in the number of cesarean sections accompanied by the incidence of post-sectional caesarean section(CS) wound infections, where data obtained about 90% of post-C-section morbidity is caused by surgical wound infections. Post CS suture wound healing is influenced by several factors, one of which is the consumption of high protein nutrition such as eggs. This study aimed to determine post-SC wound healing among postpartum women who consumed boiled eggs at the RSIA Pasutri, Bogor in 2021. This research method was a Quasy Experiment Design with a post-test approach with Control Group. The total population was 30 postpartum women post CS, with a sample of 15 experimental groups and 15 control groups taken by purposive sampling, while data analysis used parametric test is Independent T-Test. The results of the study found that post CS postpartum women who consumed boiled eggs all respondents experienced post CS ound healing with good wounds which was 15 respondents (100%) compared to those who did not consume boiled eggs which was only 8 respondents (53.3%) experienced good wound healing. while the others experienced poor wound healing which was 7 respondents (46.7%). Based on the Independent T-Test statistical test in the experimental and control groups, the results of p value = 0.002 <0.05, thus there was a difference in post-SC wound healing between experiment and control group. The results of this study can be used as input in accelerating wound healing.